As much as necessary, as little as possible : Indexing knowledge in vocational education and training research via the automated alignment of literature to projects within a knowledge management system - Linten, Markus [Verfasser]; Dücker, Sandra [Verfasser] (Bundesinstitut für Berufsbildung, 2006)
"In order to make VET research knowledge accessible to a wider circle of users and working in conjunction with the Internet editorial team of the Federal Institute for Vocational Education and Training (BIBB), the "Communication and Information System Vocational Education and Training" (KIBB) Project has developed a so-called "knowledge map", which uses a thematically structured catalogue to present German VET research issues, activities and results. The following focuses on the example of the Literature Database for Vocational Education and Training (LDBB) for the purposes of demonstrating how the collation of information takes place from systems with widely differing requirements in terms of processing of information and how such a process creates added value for users. This article will firstly present the LDBB as a documentation system, its main thematic areas and how content can be indexed before moving on to provide an explanation of the automated display of references and the ensuing added value for the "knowledge map". The final section will deal with the perspectives for and the further development of the LDBB documentation system and the information stored within the KIBB portal "knowledge map". (extract; BIBB-Doku)
Keywords: S 5.2 Wissensmanagement; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); L 4.2.4 Expertennetzwerke / Wissensplattformen; Wissensmanagement; Wissenstransfer; Informationssystem; Literaturdokumentation; Berufsbildungsforschung; Bundesinstitut für Berufsbildung